2021
DOI: 10.1038/s41598-021-90875-3
|View full text |Cite
|
Sign up to set email alerts
|

The association between implicit and explicit affective inhibitory control, rumination and depressive symptoms

Abstract: Inhibitory control underlies one’s ability to maintain goal-directed behavior by inhibiting prepotent responses or ignoring irrelevant information. Recent models suggest that impaired inhibition of negative information may contribute to depressive symptoms, and that this association is mediated by rumination. However, the exact nature of this association, particularly in non-clinical samples, is unclear. The current study assessed the relationship between inhibitory control over emotional vs. non-emotional inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…Differences between groups in food‐related inhibitory control did not remain significant after controlling for co‐occurring psychopathology (i.e., depression, anxiety and stress), which should be considered when interpreting the findings. In fact, previous studies have found evidence for an association between anxiety and depressive symptoms and poor executive functioning (Billingsley‐Marshall et al., 2013; Shimony et al., 2021). Future studies should take into account the presence of comorbid symptomatology as possible variables influencing cognitive performance.…”
Section: Discussionmentioning
confidence: 98%
“…Differences between groups in food‐related inhibitory control did not remain significant after controlling for co‐occurring psychopathology (i.e., depression, anxiety and stress), which should be considered when interpreting the findings. In fact, previous studies have found evidence for an association between anxiety and depressive symptoms and poor executive functioning (Billingsley‐Marshall et al., 2013; Shimony et al., 2021). Future studies should take into account the presence of comorbid symptomatology as possible variables influencing cognitive performance.…”
Section: Discussionmentioning
confidence: 98%
“…This association may have clinical utility in identifying and predicting depressive symptoms in preadolescence. For example, response inhibition difficulties may be used as an objective tool for assessing depressive symptoms alongside self‐report measures, with the potential to predict the onset of depressive symptoms (Shimony et al., 2021). Furthermore, support aimed at training effective response inhibition ability in preadolescence, such as using cognitive training programs (Koster et al., 2017; Woolf et al., 2022), may help prevent or lower depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Poor inhibitory control (IC) is a hypothesized vulnerability for both depression and ruminative thinking, though the effect of rumination on IC and depression may be indirect [ 17 , 18 ]. IC is one of various higher-level cognitive processes, grouped under the term cognitive control, which regulate lower-level cognitive processes, such as motor control [ 17 ].…”
Section: Inhibitory Controlmentioning
confidence: 99%